Relationship between Education Expenditure, Capital, Labor Force and Economic Growth in Malaysia - Norimah Rambeli, Ramli; Emilda, Hashim; Dayang Affizzah, Awang Marikan (http://www.hrmars.com/, 2016)
Educational institutions play important role in producing highly educated communities. Investment in education an opportunities expansion to obtain higher education has become main economic development agenda in many countries, including Malaysia. Therefore, this study is conducted to examine the relationship between government expenditure and economic growth from 1970 to 2013. By using Cobb-Douglas Production Function in developing Multiple Regression Linear Model, the results show a significant and positive relationship between education expenditure and Malaysian economic growth. The findings further suggest that capital and labor force also influence economic growth in the long run.